Early childhood neurodevelopmental outcome after open prenatal spina bifida aperta repair. (23rd July 2021) - Hepp, Zehra S; Haas, Verena M; Latal, Beatrice; Meuli, Martin; Möhrlen, Ueli; Schauer, Sonja M; Steinfeld, Robert; Padden, Beth A; Wille, David A
Abstract : Aim: To investigate neurodevelopmental outcome of children with open prenatal spina bifida aperta (SBA) repair. Method: Prenatal SBA repair was performed in 130 fetuses at the Zurich Center between 2010 and 2019. Seventy‐seven children underwent 1 year assessment with the Griffiths Mental Developmental Scales (Griffiths) and 65 with the Bayley Scales of Infant and Toddler Development, Third Edition (Bayley‐III) at 2 years. Anatomical and functional level and ambulation status were assessed. Descriptive statistics and multiple linear regression analyses for risk factors were performed. Results: The Bayley‐III cognition composite score in children with prenatal SBA repair was within normal limits but lower compared to population norms (mean=95.15, SD=14.683 vs norm=100, SD=15, p =0.01). Fine motor development (mean=9.58, SD=2.744, p =0.227) was typical while gross motor development was lower than the norm (mean=3.02, SD=2.758 vs norm=10, SD=3, p <0.001). Griffiths developmental quotient subscales correlated significantly with corresponding Bayley‐III scores (all p <0.001, r =0.519–0.594). At 2 years, 50.8% could walk. Interpretation: Children with non‐trial open prenatal SBA repair show favourable cognitive outcome in the low‐average range at 1 and 2 years of age. While gross motor function remained delayed, fine motor function was age appropriate. The correlation between Griffiths and Bayley‐III allows a prediction about neurodevelopmental outcome at the age of 1 year. What this paper adds Children with non‐trial open prenatal spina bifida repair show favourable cognitive outcome. Gross motor function remains impaired, while fine motor function is age appropriate. At 2 years of age, 50.8% of children were walking. Neurodevelopmental testing correlated between 1 (Griffiths Mental Developmental Scales) and 2 (Bayley Scales of Infant and Toddler Development, Third Edition) years. What this paper adds: Children with non‐trial open prenatal spina bifida repair show favourable cognitive outcome. Gross motor function remains impaired, while fine motor function is age appropriate. At 2 years of age, 50.8% of children were walking. Neurodevelopmental testing correlated between 1 (Griffiths Mental Developmental Scales) and 2 (Bayley Scales of Infant and Toddler Development, Third Edition) years. This original article is commented by Joyeux and Belfort on page 1243 of this issue.